2019
DOI: 10.1002/evl3.147
|View full text |Cite
|
Sign up to set email alerts
|

The “Law of Brevity” in animal communication: Sex-specific signaling optimization is determined by call amplitude rather than duration

Abstract: The efficiency of informational transfer is one of the key aspects of any communication system. The informational coding economy of human languages is often demonstrated by their almost universal fit to Zipf's “Law of Brevity,” expressing negative relationship between word length and its usage frequency. Animal vocal systems, however, provided mixed results in their adherence to this relationship, potentially due to conflicting evolutionary pressures related to differences in signaling range and communicationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 63 publications
(131 reference statements)
0
28
0
Order By: Relevance
“…Therefore, it is possible that we did not find support for Zipf's Law of abbreviation because selective forces which oppose compression, and maximize transmission in noisy environments, were more important in shaping male solo phrase organization. As Demartsev et al [39] royalsocietypublishing.org/journal/rsos R. Soc. Open Sci.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is possible that we did not find support for Zipf's Law of abbreviation because selective forces which oppose compression, and maximize transmission in noisy environments, were more important in shaping male solo phrase organization. As Demartsev et al [39] royalsocietypublishing.org/journal/rsos R. Soc. Open Sci.…”
Section: Discussionmentioning
confidence: 99%
“…But, Zipf's Law of abbreviation was not found in the vocal repertoire of two new world monkeys: common marmosets (Callithrix jacchus) and golden-backed uakaris (Cacajao melanocephalus) [37], ravens (Carvus corax) [38] or the full body gestures of chimpanzees [28] which may be related to the small repertoire sizes in these animals, or differences in function or context of use [37]. A recent study on rock hyraxes (Procavia capensis) found support for Zipf's Law of abbreviation in male but not female vocal repertoires, and also found a negative relationship between call amplitude and call usage, and the authors propose that for long-distance communication, costs of call amplitude may be more important than call duration [39].…”
Section: Introductionmentioning
confidence: 99%
“…Three laws, in particular, have garnered a substantial amount of interest: Zipf's Law (wherein the most commonly used word will occur approximately twice as often as the next most common word [8]), Zipf's Law of Abbreviation (elements used more frequently in a communication system are shorter [8]) and Menzerath's Law (the greater the whole, the smaller its constituents [9]). There has been increasing interest in applying these statistical laws outside of human language [10][11][12][13][14][15][16][17][18][19][20][21]. These statistical laws reflect compression, and it has been proposed that compression is a universal principle not just in vocal communication but in behaviour more broadly [1].…”
Section: Introductionmentioning
confidence: 99%
“…The authors attributed lack of conformity to Zipf's Law in one chickadee species (but not the other) to differences in social complexity [ 14 ]. One of the first-documented tests of Zipf's Law of Abbreviation was also in black-capped chickadees [ 14 ], and subsequent analyses showed adherence to Zipf's Law of Abbreviation in dolphin surface behaviours [ 25 ], Formosan macaque vocalizations [ 16 ], the short-range vocalizations of four bat species [ 17 ], a subset of chimpanzee gestures [ 12 ], male (but not female) rock hyrax vocalizations [ 18 ], penguin vocalizations [ 19 ], and in note [ 20 ] but not phrase usage [ 21 ] in male gibbon solos. Adherence to Zipf's Law of Abbreviation was not seen in the vocal repertoire of two New World monkeys (common marmosets and golden-backed uakaris [ 15 ]), ravens [ 6 ] or the full-body gestures of chimpanzees [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Any communicative channel must increase in complexity if it is to contain more information, but complex communication places higher cognitive and motor demands on the animal, both for meaningful signal production, and accurate signal interpretation (Fedurek et al., 2017; Seyfarth & Cheney, 2010). There is considerable evidence that many animal species balance these trade‐offs according to empirical laws of information encoding, such as the Menzerath‐Altmann law (Gustison & Bergman, 2017; Gustison et al., 2016; Heesen et al., 2019), Zipf's law of brevity/abbreviation (Demartsev et al., 2019; Semple et al., 2010) and Zipf's law of least effort (this study; Allen et al., 2019; Ferrer‐i‐Cancho & McCowan, 2009). In itself, conforming to such laws does not indicate that an animal possesses true linguistic abilities, rather, that the evolutionary history of the species has had to contend with conflicting pressures of information content and cognitive‐motor constraints.…”
Section: Discussionmentioning
confidence: 99%